Tracking the transition of sustainable entrepreneurship: from a bibliometric analysis to current research trends and future research directions - Mani Jindal; Mayank Kumar; Nirakar Nath Pandey; Vijayalaxmi Rajendran; Pankaj Dhaundiyal; Priyanshu Sharma; Ramji Nagariya; Chandraketu Singh (Discover Sustainability)
Abstract Sustainability in family businesses is an increasingly important and ever-evolving topic in business research, due to the demands of sustainable development agendas for all types of companies. This study conducts a comprehensive literature review on sustainable entrepreneurship (SE) using bibliometric analysis, content analysis, and a systematic literature review. The systematic literature review helps in finding the 554 SE-related articles. The bibliometric and content analysis was carried out on these articles. The study also analyzed the recent articles separately to identify research gaps and current trends. The study identifies the research to be diversified in six broad themes: ‘sustainable entrepreneurial enterprise’, ‘relationship between social entrepreneurship and the sustainable ecosystem’, ‘publications from different angles’, ‘model, framework, and conceptual papers’, ‘involvement of new entrants’, and ‘influence of financial support’ and ‘green start-ups’. The future research directions will help scholars identify clear research gaps to explore this area further. Researchers can focus on green agritourism, advanced recycling methods, eco-centric models, frameworks, operational procedures, financing partnerships, and transitioning into the digital era.